EXTREMAL ELECTROMECHANICAL CONTROL SYSTEM OF WATER SUPPLY PUMPS CONNECTED IN PARALLEL - Buryan, S. O.; Grishchuk, T. V. (Radio Electronics, Computer Science, Control, 2012)
The paper concerns the application of the extremal energy efficient control for two pumps connected in parallel. One of the pumps is with the controlled induction motor drive. The extremal control algorithm description, its mathematical model and the system block diagram are presented.